Media literacy for children: Empowering citizens for a mediatized world - Mateus, Julio-César (2021)
Becoming a critical user of media is a premise for citizenship in contemporary times. The use of critical thinking skills in mediatized scenarios demands developing the ability to interact with media, not only in being able to use devices, but also for understanding their socio-cultural effects. Our recent pandemic and political circumstances have raised our levels of awareness about fake news and biased media opinions. Here, I contend that we need to consider three basic arguments that should be taken into account when thinking about media literacy: Access to the internet constitutes a human right, though that is not enough, as we must develop critical media literacy skills as well; media policies should focus on the empowerment of citizens; and media literacy education policies must address the initial and continued professional learning of teachers to ensure its success.